ANALISIS PENGARUH SEKTOR UNGGULAN MENJADI PUSAT PERTUMBUHAN KABUPATEN LABUHANBATU TAHUN 2013-2017 - Zulkarnain Nasution (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2020)
Abstract This study aims to determine the dominant sector of the regional economy Labuhanbatu. Secondary data were obtained the form of time series from the Gross Regional Domestic Product (GRDP) of Labuhanbatu and North Sumatera province from 2013-2017 to determine the most prominent sector using Typology Klassen, LQ, shift and MRP methods. The economic sectors were divided into four groups based on their large contribution and economic growth rate namely prominent, growing, potential and underdeveloped. The result showed that the Labuhanbatu and North Sumatera province were prominent in the agriculture, mining and quarrying, Transportation and Storage, Accommodation and Food Service Activities, financial, communication, and education sector